2020
DOI: 10.1177/2515127420917355
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Literature Review of Teacher Entrepreneurship

Abstract: Teacher entrepreneurship has received increasing attention over the past 15 years. However, the concept remains underdeveloped and understudied. To fill this gap in the literature, we aim to conceptualize teacher entrepreneurship through a systematic literature review of current scholarly work on the topic. Results of our study provide competencies and traits which are commonly attributed to teacher entrepreneurs, along with actions which they carry out. Teacher entrepreneurs are socially motivated individuals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(44 citation statements)
references
References 45 publications
(106 reference statements)
2
32
0
Order By: Relevance
“…The characteristics that were most often mentioned by respondents during their interviews and after participating in each of the IWLs were creativity, teamwork, openmindedness, innovation and passion, in line with authors such as Keyhani and Kim (2020); Raine and Pandya (2019) and Syae (2020). The characteristics that the participants repeated every time they were asked, in addition to the previous ones, included motivation, hard work, risk-taking, ability to deal with challenges, taking the initiative, proactivity, organisation skills, perseverance, and leadership and communication skills, as well as an ability to adapt, be positive and make decisions.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…The characteristics that were most often mentioned by respondents during their interviews and after participating in each of the IWLs were creativity, teamwork, openmindedness, innovation and passion, in line with authors such as Keyhani and Kim (2020); Raine and Pandya (2019) and Syae (2020). The characteristics that the participants repeated every time they were asked, in addition to the previous ones, included motivation, hard work, risk-taking, ability to deal with challenges, taking the initiative, proactivity, organisation skills, perseverance, and leadership and communication skills, as well as an ability to adapt, be positive and make decisions.…”
Section: Discussionmentioning
confidence: 81%
“…Considering the characteristics of entrepreneurs, it could be concluded that the students were not misdirected, since there are a large number of studies on the characteristics of entrepreneurs, but none has been able to validate the characteristics of a successful entrepreneur (Bucardo et al, 2015), successfully conceptualised the term teacherpreneur (Keyhani and Kim, 2020), or determined the basic skills of the teacherpreneur.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from broadening the scope of the study to an international context, it would be interesting to pursue further research regarding the characteristics of entrepreneurs and/or innovators from an educational perspective, as there is still much to be done in this area. A highly current systematic review of teacher entrepreneurship could be considered as a starting point (Keyhani and Kim, 2020). It would also be a very useful to adopt a common, consensual definition of innovation and entrepreneurship, together with entrepreneurial and innovative competences.…”
Section: Limitations and Further Lines Of Researchmentioning
confidence: 99%
“…Entrepreneurship is a growing public concern worldwide, and it has gained scholars' attention from around the world (Keyhani & Kim, 2020;Ratten & Jones, 2020). The underlying rationale is that ABOUT THE AUTHOR Djoko Dwi Kusumojanto is an Associate professor specializing on Business educational, entrepreneurship education, and entrepreneurship at Faculty of Economics, Universitas Negeri Malang, Indonesia.…”
Section: Introductionmentioning
confidence: 99%